Pupils' development: Policy enactment in Swedish school-age educare - Björn Haglund (Taylor & Francis Group, 2023)
ABSTRACTThe historical roots of what is now a modern Swedish school-age educare (SAEC) were formed from a social pedagogical starting point in which children's social development, freedom and well-being were prioritized. SAEC has now become more focused on an educational pedagogical assignment and has been incorporated into the Swedish curriculum. SAECs could therefore be seen as institutions under reconstruction, in that their current work is formed in what can be regarded as a transition period. This transition could imply new points of departure concerning work practices and forms of documentation, both of that could challenge older traditions. Using policy enactment theory as a methodology, this case study discusses the work practices and forms of documentation that are in use now, with a specific focus on the latter. The main purpose of the article is to explore and develop SAEC staff's points of departure for developing their documentation and assessments and how the new curriculum assignment is enacted in the context of SAEC's pedagogical practices. The study's findings show that the enactment process could be seen as an initiative based on local needs for clarity. The developed documentation and assessment practices are described as a cultural shift away from former practices.